2006
DOI: 10.1577/t05-175.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Age Determination and Spatial Patterns of Growth in Red Sea Urchins in Southeast Alaska

Abstract: The goals of this study were to characterize growth of the commercially harvested red sea urchin Strongylocentrotus franciscanus in southeastern Alaska and test the validity of an aging technique. We aged urchins by counting growth rings on a part (rotula) of the Aristotle's lantern complex from urchins collected at three sites. A subset of collected urchins had three or more years of size measurements from passive integrated transponder (PIT) tag data, allowing us to fit and compare PIT tag and ring-derived g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
(47 reference statements)
1
7
0
1
Order By: Relevance
“…Therefore, the shapes and AIC values can be very close or equal. Similar results have been previously described using the general model of Richards or Schnute vs. different growth submodels (Rogers-Bennett et al 2007, Flores et al 2010, Shelton et al 2006, Barreto et al 2011. The literature shows that for the multi-model inference approach applied to individual growth, it is not unusual that different candidate growth models yield equal values of AIC (Rogers-Bennett et al 2007, Flores et al 2010, Helidoniotis et al 2011).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, the shapes and AIC values can be very close or equal. Similar results have been previously described using the general model of Richards or Schnute vs. different growth submodels (Rogers-Bennett et al 2007, Flores et al 2010, Shelton et al 2006, Barreto et al 2011. The literature shows that for the multi-model inference approach applied to individual growth, it is not unusual that different candidate growth models yield equal values of AIC (Rogers-Bennett et al 2007, Flores et al 2010, Helidoniotis et al 2011).…”
Section: Discussionsupporting
confidence: 82%
“…The literature shows that for the multi-model inference approach applied to individual growth, it is not unusual that different candidate growth models yield equal values of AIC (Rogers-Bennett et al 2007, Flores et al 2010, Helidoniotis et al 2011). Several studies also have shown that the AIC estimates of the candidate growth models were very close; the magnitude of the change can be < 0.1 (Araya & Cubillos 2006, Shelton et al 2006, Farrell et al 2010, Barreto et al 2011, Grist et al 2011, Mercier et al 2011, Shuman et al 2011. Markaida et al (2005), using mark-recapture data of D. gigas, showed that the daily growth rate diminishes for older individuals; their study analyzed squid between 46 and 80.7 cm ML, and the daily growth rate changed from 1.5 to 1.0 mm d −1…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These tags allowed identification of individuals held in a single tank and have been used successfully in studies of sea urchins (Hagen, 1996;Shelton et al, 2006). These tags allowed identification of individuals held in a single tank and have been used successfully in studies of sea urchins (Hagen, 1996;Shelton et al, 2006).…”
Section: Adult Acclimation Limits Studymentioning
confidence: 99%
“…Laboratory studies have demonstrated the potential of PIT tags in measuring growth and survival, without detectable adverse effects, in 2 species of sea urchin: Strongylocentrotus droebachiensis (Hagen 1996) and Evechinus chloroticus (Woods & James 2005). However, the use of PIT tags in field studies has largely been tempered by the lack of underwater readers (Duggan & Miller 2001), and is limited to 2 studies of growth and age determination (RogersBennett et al 2003, Shelton et al 2006. Recently, the development of smaller and more independent readers, which can be encased in a waterproof housing, has permitted their usage underwater.…”
Section: Introductionmentioning
confidence: 99%